2007
DOI: 10.1371/journal.pone.0000916
|View full text |Cite
|
Sign up to set email alerts
|

A Multicassette Gateway Vector Set for High Throughput and Comparative Analyses in Ciona and Vertebrate Embryos

Abstract: BackgroundThe past few years have seen a vast increase in the amount of genomic data available for a growing number of taxa, including sets of full length cDNA clones and cis-regulatory sequences. Large scale cross-species comparisons of protein function and cis-regulatory sequences may help to understand the emergence of specific traits during evolution.Principal FindingsTo facilitate such comparisons, we developed a Gateway compatible vector set, which can be used to systematically dissect cis-regulatory seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
121
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(122 citation statements)
references
References 51 publications
0
121
0
Order By: Relevance
“…The in vivo assembly methods described to date have proceeded with efficiencies that are simply too low (≤10 2 colonies) to be useful for the one-pot assembly of collections of pathways. Even after modification and optimization, most in vitro assembly techniques based on restriction digestion and ligation or on enzymatic recombination typically display profound losses in cloning efficiency for ≥3 fragments (≤10 3 colonies per reaction) (37,38). Several particularly efficient in vitro approaches (8), notably in vitro recombination (12)(13)(14), could theoretically generate libraries of ∼10 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo assembly methods described to date have proceeded with efficiencies that are simply too low (≤10 2 colonies) to be useful for the one-pot assembly of collections of pathways. Even after modification and optimization, most in vitro assembly techniques based on restriction digestion and ligation or on enzymatic recombination typically display profound losses in cloning efficiency for ≥3 fragments (≤10 3 colonies per reaction) (37,38). Several particularly efficient in vitro approaches (8), notably in vitro recombination (12)(13)(14), could theoretically generate libraries of ∼10 4 .…”
Section: Discussionmentioning
confidence: 99%
“…A super core promoter, a synthetic intron (Arnold et al 2013), and a venus reporter gene (Roure et al 2007) were inserted between the KpnI and XbaI restriction sites of the pGL4.23 plasmid (Promega Catalog No. E8411).…”
Section: Cheq-seq Plasmid and Bait Designmentioning
confidence: 99%
“…On the other hand, such a negative effect was not observed for the multisite Gateway vector R4pGWB series, which has attB sequences in the transcribed region, suggesting that the differences in vector systems and/or attB sequences between the pDEST and R4pGWB series may be involved in the negative effect of the attB sequences. Although studies in several eukaryotes have reported that the additional sequences from the Gateway system did not interfere with the biological activity of a cloned fragment, including subcellular localization or tissue specificity, there has been no description about any effect on gene expression (Curtis and Grossniklaus 2003;Nakagawa et al 2007a, b;Roure et al 2007;Yahata et al 2005). Our results demonstrated that the Gateway linker sequences did not interfere with expected biological function, but could reduce gene expression depending on vector systems.…”
Section: Discussionmentioning
confidence: 49%